2019
DOI: 10.1111/eth.12869
|View full text |Cite
|
Sign up to set email alerts
|

Managing predators: The influence of kangaroo rat antipredator displays on sidewinder rattlesnake hunting behavior

Abstract: Upon sensing predators in their vicinity, many prey species perform antipredator displays that are thought to provide information to the predator that deters it from attacking (predator‐deterrent signals). These displays can be complex, incorporating a variety of signaling elements as well as direct physical harassment of the predator. Although the display behaviors in these communication systems are often well characterized, evidence of the efficacy of these displays in deterring predators is limited due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…2016 ; Glaudas et al. 2017 ; Whitford et al. 2019a ), we were able to notice qualitative differences in the predatory strike of rattlesnakes when in captivity or when striking an artificial target, such as a warmed mouse carcass (“non-natural” strikes).…”
Section: Discussionmentioning
confidence: 94%
“…2016 ; Glaudas et al. 2017 ; Whitford et al. 2019a ), we were able to notice qualitative differences in the predatory strike of rattlesnakes when in captivity or when striking an artificial target, such as a warmed mouse carcass (“non-natural” strikes).…”
Section: Discussionmentioning
confidence: 94%
“…As with most predator–prey encounters, the outcome of the interaction can potentially be altered by a suite of factors at multiple timepoints (as in Higham et al, ). For example, a large body of literature has shown that kangaroo rats can use predator‐deterrent signals (e.g., foot drumming, sand kicking) during the evaluation stage of the interaction to dissuade snakes from attacking (Whitford Freymiller, & Clark, , ). If the encounter does proceed to the attack stage, an ambush predator must not only accurately target prey, but also attempt to time the strike such that it can reach the prey without being detected (Casas & Steinmann, ); therefore, both strike accuracy and speed are critical factors in determining the outcome of the interaction (Clark, Tangco, & Barbour, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the thermal dependence of snake locomotor performance (Gerald et al, 2008; Stevenson et al, 1985), lower Tb may result in longer relocation of prey, leading to a lower success rate of prey ingestion due to the robbery of the carcass by other animals or due to disturbance by potential predators of the snake. Indeed, field observations on pit vipers (Clark, 2016; Kodama, personal observation; Whitford, Freymiller, & Clark, 2019) show that even when snakes successfully strike prey, the snakes sometimes fail to ingest their meals. Further studies on various aspects of foraging are strongly desired in order to gain a comprehensive understanding of thermal effects on snake–prey interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of natural encounters between a snake and its prey have been shown to be affected by various additional factors, such as distance between the snake and prey and dodging reactions and predator‐deterrent signals by the prey (Clark et al, 2012; Whitford, Freymiller, & Clark, 2019; Whitford, Freymiller, Higham, & Clark, 2019). Thus, to examine the relative importance of temperature among the various factors influencing the outcomes of such encounters, it is essential to adopt integrative, multivariate approaches.…”
Section: Introductionmentioning
confidence: 99%